40 Centuries of State and Legal Thought (review for the first Part of the textbook by O. M. Holovko and T. Ye. Kahanovska "History of the Doctrines on Law and State") - V. A. Grechenko (Law and Safety)
The authors set themselves an important task in terms of volume and depth: to reveal the value of the thoughts of their great predecessors and to bring these treasures to the minds of students of the XXI century. I am convinced that they succeeded in full. The language of the textbook, its imagery and liveliness, the success of quotations, the original author's commentary, the depth of conclusions - all these are the characteristic features of the peer-reviewed work. It has many advantages and benefits, and it is difficult to say everything in a fairly short review, but we will say one more thing. Undoubtedly, this book will help improve the training of the new generation of lawyers, give them a basis for reflection on some of the eternal problems of jurisprudence - theoretical and practical, closely related to their present and future lives. reference book on this historical and legal discipline.